Answer: 99 different faces
Step-by-step explanation:
Since a witness can clearly remember the hairline and the eyes and eyebrows of a suspect, and the
basic identification kit contains 195 hairlines, 99 eyes and eyebrows, the number of different faces that can be produced with this information will be 99
Answer:
its the third one i got that
Answer:
Statisticians use z-scores to divide the area under a curve the way people use a knife to cut pizza.
Step-by-step explanation:
Statisticians use z-scores to divide the area under a curve the way people use a knife to cut pizza.
z-score:
- A z-score is a numerical measurement which is measured in terms of standard deviations from the mean.
- Formula:
![z_{score} = \displaystyle\frac{x-\mu}{\sigma}](https://tex.z-dn.net/?f=z_%7Bscore%7D%20%3D%20%5Cdisplaystyle%5Cfrac%7Bx-%5Cmu%7D%7B%5Csigma%7D)
- If a z-score is 0, it tells that the data point is same as the mean.
- Area under the normal curve is 1.
Answer:
1/2
Step-by-step explanation:
x + 9 = -15x = [1]
x - x + 9 = -15x -x = 1
9 - 1 = -16x
8 = 16x
8/16 = 16/16x
1/2 = x
Hope this helps
Answer:
Hence, the particular solution of the differential equation is
.
Step-by-step explanation:
This differential equation has separable variable and can be solved by integration. First derivative is now obtained:
![f'' = x - \frac{3}{2}](https://tex.z-dn.net/?f=f%27%27%20%3D%20x%20-%20%5Cfrac%7B3%7D%7B2%7D)
![f' = \int {\left(x-\frac{3}{2}\right) } \, dx](https://tex.z-dn.net/?f=f%27%20%3D%20%5Cint%20%7B%5Cleft%28x-%5Cfrac%7B3%7D%7B2%7D%5Cright%29%20%7D%20%5C%2C%20dx)
![f' = \int {x} \, dx -\frac{3}{2}\int \, dx](https://tex.z-dn.net/?f=f%27%20%3D%20%5Cint%20%7Bx%7D%20%5C%2C%20dx%20-%5Cfrac%7B3%7D%7B2%7D%5Cint%20%5C%2C%20dx)
, where C is the integration constant.
The integration constant can be found by using the initial condition for the first derivative (
):
![1 = \frac{1}{2}\cdot 4^{2} - \frac{3}{2}\cdot (4) + C](https://tex.z-dn.net/?f=1%20%3D%20%5Cfrac%7B1%7D%7B2%7D%5Ccdot%204%5E%7B2%7D%20-%20%5Cfrac%7B3%7D%7B2%7D%5Ccdot%20%284%29%20%2B%20C)
![C = 1 - \frac{1}{2}\cdot 4^{2} + \frac{3}{2}\cdot (4)](https://tex.z-dn.net/?f=C%20%3D%201%20-%20%5Cfrac%7B1%7D%7B2%7D%5Ccdot%204%5E%7B2%7D%20%2B%20%5Cfrac%7B3%7D%7B2%7D%5Ccdot%20%284%29)
![C = -1](https://tex.z-dn.net/?f=C%20%3D%20-1)
The first derivative is
, and the particular solution is found by integrating one more time and using the initial condition (
):
![y = \int {\left(\frac{1}{2}\cdot x^{2}-\frac{3}{2}\cdot x -1 \right)} \, dx](https://tex.z-dn.net/?f=y%20%3D%20%5Cint%20%7B%5Cleft%28%5Cfrac%7B1%7D%7B2%7D%5Ccdot%20x%5E%7B2%7D-%5Cfrac%7B3%7D%7B2%7D%5Ccdot%20x%20-1%20%20%5Cright%29%7D%20%5C%2C%20dx)
![y = \frac{1}{2}\int {x^{2}} \, dx - \frac{3}{2}\int {x} \, dx - \int \, dx](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B1%7D%7B2%7D%5Cint%20%7Bx%5E%7B2%7D%7D%20%5C%2C%20dx%20-%20%5Cfrac%7B3%7D%7B2%7D%5Cint%20%7Bx%7D%20%5C%2C%20dx%20-%20%5Cint%20%5C%2C%20dx)
![y = \frac{1}{6} \cdot x^{3} - \frac{3}{4}\cdot x^{2} - x + C](https://tex.z-dn.net/?f=y%20%3D%20%5Cfrac%7B1%7D%7B6%7D%20%5Ccdot%20x%5E%7B3%7D%20-%20%5Cfrac%7B3%7D%7B4%7D%5Ccdot%20x%5E%7B2%7D%20-%20x%20%2B%20C)
![C = 0 - \frac{1}{6}\cdot 0^{3} + \frac{3}{4}\cdot 0^{2} + 0](https://tex.z-dn.net/?f=C%20%3D%200%20-%20%5Cfrac%7B1%7D%7B6%7D%5Ccdot%200%5E%7B3%7D%20%2B%20%5Cfrac%7B3%7D%7B4%7D%5Ccdot%200%5E%7B2%7D%20%2B%200)
![C = 0](https://tex.z-dn.net/?f=C%20%3D%200)
Hence, the particular solution of the differential equation is
.